The Effect of Osteocalcin in Middle-Age Women With and Without Type2 Diabetes Mellitus - Hadeer I. Jassim; Ammar L. Hussein (Diyala Journal of Medicine, 2024)
Background: Diabetes mellitus is a chronic disease that affects people of all ages. It's caused by deficiencies in insulin action and secretion, leading to long-term hyperglycemia. This can harm key organs such as the kidneys, heart, eyes, nerves, and blood vessels. Managing diabetes requires significant lifestyle changes and can impact both the patient and their family. Small and bone-specific, osteocalcin (OCN) is a non-collagen protein that is mostly present in bone. It is a sensitive marker of bone formation and primarily attaches to the extracellular matrix of bone after being carboxylated. Small amounts of OCN are also released into the bloodstream, where it aids in glucose and fat metabolism. Objective: Our study aimed to examine the effect of Osteocalcin, Parathyroid hormone, Estrogen and HbA1c on middle-aged women who had type 2 diabetes compared to those who did not. Patients and Methods: The study involved 90 middle-aged women, including 60 with type 2 diabetes, and 30 healthy women. The Sandwich enzyme-linked immunosorbent assay was used to measure OCN, PTH, and E2 hormone levels in women with and without type 2 diabetes. HbA1c levels were measured using the Cobos system. The statistical analysis was performed using SPSS software. Results: In T2DM women, serum OCN, PTH, E2, and HbA1c levels were compared with non-diabetic women. T2DM women had significantly lower levels of serum OCN and PTH, and significantly higher levels of HbA1c than healthy women. Serum E2 levels were also significantly lower in T2DM women. OCN had a positive correlation with HbA1c and negative correlations with PTH and E2. Conclusion: Significant change was detected in this study in the level of OCN, PTH and E2 between patients and controls. Investigations of serum OCN can be participated in the future as predictive marker for osteoporosis in diabetic women. Keywords: Osteocalcin, parathyroid hormone, estrogen, Type2 diabetes mellitus.